Cyanobacterial Toxins as Allelochemicals with Potential Applications as Algaecides, Herbicides and Insecticides - Berry, John P. (Molecular Diversity Preservation International, 2008)
Cyanobacteria (“blue-green algae”) from marine and freshwater habitats are known to produce a diverse array of toxic or otherwise bioactive metabolites. However, the functional role of the vast majority of these compounds, particularly in terms of the physiology and ecology of the cyanobacteria that produce them, remains largely unknown. A limited number of studies have suggested that some of the compounds may have ecological roles as allelochemicals, specifically including compounds that may inhibit competing sympatric macrophytes, algae and microbes. These allelochemicals may also play a role in defense against potential predators and grazers, particularly aquatic invertebrates and their larvae. This review will discuss the existing evidence for the allelochemical roles of cyanobacterial toxins, as well as the potential for development and application of these compounds as algaecides, herbicides and insecticides, and specifically present relevant results from investigations into toxins of cyanobacteria from the Florida Everglades and associated waterways.